Major causes of lift breakdown in high rise building at Shah Alam / Mohd Ferdaus Sinuzulan Shahalun - Sinuzulan Shahalun, Mohd Ferdaus (Faculty of Architecture, Planning and Surveying, 2009)
Lift systems is one of the most important vertical transportation systems in a multi storey and/or high rise building. Its positioning placement needs to be of exacting standards as it affects the efficiency of movement for the building's occupants. The title of this research is "Major Causes of Lift Breakdown in High Rise Building at Shah Alam" covers a little bit on the aspects of lift maintenances of component, planning of the maintenances and to find out the cause of lift breakdown. The case study building are includes Menara MRCB, Bangunan Darul Ehsan and Plaza Perangsang. The aim of this research is to identify the major cause of lift breakdown and purpose to select the relevant method to reduce and furthermore to avoid the lift breakdown at the selected case study. This research also to identify that any component of the lift that usually need the maintenance purpose to achieved the target of research. This research included how to indentified or find any error reach out from all component of elevator. The understanding about lift components and major causes will help to integrate the planning and implementation of the maintenance works. The method for get any results and finding using by questionnaire and observation at the case study and analyze the question with use the Microsoft excel for get pie chart and gathered all information from the respondents.